Carbon-deficient high-entropy (Zr0.17Nb0.2Ta0.2Mo0.2W0.2)C0.89: A potential high temperature and vacuum wear-resistant material. (February 2023) - Li, Jicheng; Zhang, Qiangqiang; Chen, Shuna; Fan, Hengzhong; Song, Junjie; Su, Yunfeng; Hu, Litian; Zhou, Yanchun; Zhang, Yongsheng
Graphical abstract: Highlights: An effective design strategy is proposed to improve the toughness and vacuum high-temperature tribological properties of high-entropy carbides by introducing vacancies and Mo. The fracture toughness of (Zr0.17 Nb0.2 Ta0.2 Mo0.2 W0.2 )C0.89 is up to 4.5 ± 0.2 MPa·m 1/2 due to the introduction of vacancies. The (Zr0.17 Nb0.2 Ta0.2 Mo0.2 W0.2 )C0.89 presented brilliant friction-reducing and wear-resistant properties, with the lowest friction coefficient (0.31 ± 0.01) and low wear rate (10 -6 mm 3 /Nm) at 900 °C. The superior tribological properties were attributed to the formation of low-hardness oxidation products containing lubricating phase MoO3 . Abstract: High-entropy carbides are promising materials as sliding structural components in ultra-high temperature environments due to their good phase stability and excellent mechanical properties. However, the tribological behaviors under coupling conditions of high temperature and vacuum environment have not been deeply evaluated. To fill such a gap, the high-temperature tribological properties of carbon-deficient high-entropy (Zr0.17 Nb0.2 Ta0.2 Mo0.2 W0.2 )C0.89 (HEC0.89 ) prepared by using five binary carbides (ZrC, NbC, TaC, Mo2 C, and WC) as starting materials were investigated. The microhardness and fracture toughness of HEC0.89 were 21.3 ± 0.5 GPa and 4.5 ± 0.2 MPa·m 1/2 . Most importantly, HEC0.89 exhibited low wear rate (lower than an order of 10 -6 mm 3 /Nm) under vacuum environments from room temperature (RT) to high temperatures. Moreover, the lowest friction coefficient (0.31 ± 0.01) was obtained at 900 °C, which is attributed to the transferring of films consisting of low hardness oxidation products. These results clearly demonstrate the prospective for the application of high-entropy carbides as sliding parts in high-temperature and vacuum environments.